PENGARUH WARNA LOGO BRANDTERHADAP BRAND PERSONALITY - Gracia Diva Chandra; Laurentia Verina Halim S.; Listyo Yuwanto (Perpustakaan Universitas Surabaya, 2018)
Abstract - Brand personality is one of the most effective communications and promotion tool, which has the ability to establish consumer loyalty. Hence, it should be “designed” by utilizing the brand logo. Brand logo, particularly its color, can be manipulated to establish certain brand personality dimensions which can also attract the consumers. This research’s aim is to find further impact of logo colors towards brand personality. According to the results, it was found out that yellow color affects the construction of excitement and sincerity dimensions of brand personality. White color has the ability to affect the construction of peacefulness and sophistication dimensions. Meanwhile, the competence dimension is affected by four colors, blue, black, red, and white. However, the green colored logo wasn’t affecting any brand personality dimensions. These colors were associated with certain characteristics representing certain brand personality dimensions. Discerning the color’s impact towards brand personality, both logo designer and corporations might take a proper logo color application into consideration for creating or designing a brand logo that match its brand personality.